In vitro metabolism of canagliflozin in human liver, kidney, intestine microsomes, and recombinant uridine diphosphate glucuronosyltransferases (UGT) and the effect of genetic variability of UGT enzymes on the pharmacokinetics of canagliflozin in humans. (20th May 2015) - Francke, Stephan; Mamidi, Rao N. V. S.; Solanki, Bhavna; Scheers, Ellen; Jadwin, Andrew; Favis, Reyna; Devineni, Damayanthi
Abstract O‐glucuronidation is the major metabolic elimination pathway for canagliflozin. The objective was to identify enzymes and tissues involved in the formation of 2 major glucuronidated metabolites (M7 and M5) of canagliflozin and subsequently to assess the impact of genetic variations in these uridine diphosphate glucuronosyltransferases (UGTs) on in vivo pharmacokinetics in humans. In vitro incubations with recombinant UGTs revealed involvement of UGT1A9 and UGT2B4 in the formation of M7 and M5, respectively. Although M7 and M5 were formed in liver microsomes, only M7 was formed in kidney microsomes. Participants from 7 phase 1 studies were pooled for pharmacogenomic analyses. A total of 134 participants (mean age, 41 years; men, 63%; white, 84%) were included in the analysis. In UGT1A9*3 carriers, exposure of plasma canagliflozin (Cmax, ss, 11%; AUCτ, ss, 45%) increased relative to the wild type. An increase in exposure of plasma canagliflozin (Cmax, ss, 21%; AUCt, ss, 18%) was observed in participants with UGT2B4*2 genotype compared with UGT2B4*2 noncarriers. Metabolites further delineate the role of both enzymes. The pharmacokinetic findings in participants carrying the UGT1A9*3 and UGT2B4*2 allele implicate that UGT1A9 and UGT2B4 are involved in the metabolism of canagliflozin to M7 and M5, respectively.